ASSESSING THE RETURNS TO SCALE: EVIDENCE FROM FISH FARMERS IN ILORIN, KWARA STATE - N.A. Jatto (Russian Journal of Agricultural and Socio-Economic Sciences, 2013)
This study assesses the returns to scale as evidenced from fish farmers in Ilorin, Kwara. A random sampling technique was adopted in selecting 120 fish farmers from fish farmers association of Nigeria Ilorin branch list. The data for the study were collected with the use of well structured questionnaire. The result showed the fish farmers were relatively technically efficient in their use of resources, with a mean technical inefficiency of 40%. The result also showed that 73% of the fish farmers exhibited increasing returns to scale. On the average; numbers of fingerlings, feeds and labour had slacks of 0.0, 6.5 and 0.4 respectively. These imply that inputs could be decreased by those units and still produce the same level of output. Thus, the fish farmers are said to be inefficient in input usage by the said values. It was concluded that though average cost is expected to decrease as output increases there is still room for improvement in productivity of fish farms. With this high level of returns to scale in fish farming, it is recommended that this information should be spread to all the farmers in the study area and other surrounding communities.